Strong metal–metal interaction and bonding nature in metal/oxide interfaces with large mismatches. (15th October 2019) - Li, Hongping; Saito, Mitsuhiro; Chen, Chunlin; Inoue, Kazutoshi; Akagi, Kazuto; Ikuhara, Yuichi
Abstract: Metal/oxide heterointerfaces are ubiquitous in functional materials, and their microstructures frequently govern the macroscopic properties. It has been believed that the interfacial interactions are very weak at incoherent interfaces with large mismatches. Combining atomic-resolution scanning transmission electron microscopy with density functional theory calculations, we investigated the interaction and bonding reconstruction at Pd/ZnO{0001} interfaces, which have large mismatches. Molecular beam epitaxy was employed to grow Pd films on clean Zn-terminated ZnO(0001) and O-terminated ZnO(000 1 ¯ ) polarized surfaces. Atomically sharp Zn-terminated interfaces formed on both substrates, and the large lattice misfits between them were not strongly accommodated, suggesting the formation of incoherent regions. The interfacial atoms were located almost at bulk lattice points in the stoichiometric Zn-terminated Pd(111)/ZnO(0001) structure, whereas the interfacial Pd and Zn atoms underwent relatively large relaxations on the interfacial plane in the nonstoichiometric Zn-terminated Pd(111)/ZnO( 000 1 ¯ ) interface. Effective Pd–Zn chemical bonds were formed across both interfaces, but the bonding mechanisms were quite different, depending on the local atomic geometry. The Pd–Zn bonds exhibited site-dependent characteristics and gradually transitioned from covalent to ionic at the Pd(111)/ZnO(0001) interface, whereas most of Pd–Zn bonds exhibited strong covalent behavior at the Pd/ZnO( 000 1 ¯ ) interface. The adhesive energies indicated that the Zn-terminated Pd/ZnO( 000 1 ¯ ) interface is energetically preferable to the Zn-terminated Pd/ZnO(0001) interface. Thus, the interfacial interaction can be strong and direct metal–metal interactions can play a critical role in metal/oxide heterointerfaces with large mismatches, opening up a new avenue for understanding the origins of interface-related issues. Graphical abstract: Image 1